Análisis de cultivos hortícolas como alternativa en la producción agrícola en la región costa del Ecuador - Suarez Caicedo, Jomaira Beatriz (2020)
In Ecuador, medium and small farmers are dedicated to growing vegetables, in the agricultural context we can define vegetables as those herbaceous plants, grouped as: legumes, legumes, cabbages, bulbs, vegetables, with different life cycles: short, annual, semi-annual and perennial, most of the horticultural production is carried out in the open air, the horticultural surface under greenhouse is minimal, there are around 300 ha throughout the country, in the coastal areas they are mostly dedicated to the production of monocultures such as bananas, coffee, cocoa, rice, corn and soybeans, leaving aside the production of vegetables where their production is minimal. The information obtained was made using the analysis, synthesis and summary technique, in order for the reader to know the production of vegetables in the coastal region and how important it is to produce vegetables since it is the daily diet of all families.